ANALISIS KETERAMPILAN KOMUNIKASI DAN KETERAMPILAN KOLABORASI MAHASISWA PENDIDIKAN BIOLOGI - Thahir, Rahmatia (FKIP, Universitas Muslim Maros, 2024)
Abstract The 21 st century skills that students must have include Critical Thinking, Creativity, Communication, and Collaboration, which is often abbreviated as 4C. Communication skills orally and in writing is one of the competencies in dealing with today's life. Based on the results of observations of Biology Education students at the Muhammadiyah University of Makassar, it shows that students have not been able to communicate and collaborate well and smoothly among fellow students. The purpose of this study was to analyze collaboration skills and communication skills of Biology Education students at the University of Muhammadiyah Makassar. This type of research is Ex post Facto which will be carried out in the odd semester of 2022-2023. The instrument in this study was a questionnaire on student collaboration skills and communication skills Based on the research results found that communication skills in the good category with an average of 70.52 while collaboration skills are in the collaborative category with an average of 65.80.